Cognitive and affective implications of a STEM practice on optics in secondary education - Martínez-Borreguero, Guadalupe; Cámara Acedo, Francisco Javier; Mateos Núñez, Milagros; Naranjo Correa, Francisco Luis (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
A number of studies highlight the relevance of analysing both affective and cognitive factors in the learning of STEM content, especially in secondary education, where negative emotions and attitudes emerge towards these areas, as well as low competence levels. This research follows a quasi-experimental design with pre-tests and post-tests comparing the influence on cognitive and affective variables of a STEM practice versus an academic-expositional methodology in secondary school. The results show statistically significant differences between groups, concluding that it is essential to select active and practical methodologies that integrate scientific-technological knowledge, fostering the development of positive emotions and the ability to learn.